The effect of sustained use of Cloud-Based Business Services on organizations' performance: Evidence from SMEs in Malaysia - Al-Sharafi, Mohammed A.; Ruzaini, Abdullah Arshah; Abu-Shanab, Emad A.; Alajmi, Qasim (IEEE, 2019)
Over the decade Cloud-Based Business Services (CBBS) has emerged as a technological trend utilized in businesses towards improving the deployment of Information Communication Technology (ICT) services for competitive advantage. But, findings from prior studies suggest that there are issues related to service inconsistency which affects the effect of ICT initiatives adoption and usage in organization’ performance. Therefore, this study aims to examine the link between the sustained use of cloud-based business services and the perceived benefits of these technologies, by analyzing their effects on financial as well as non-financial benefits. Accordingly, Partial Least Squares approach to Structural Equation Modeling (PLS-SEM) was employed to evaluate the measurement model and related hypotheses. The population sample for this study consists of 415 Small and Medium-size Enterprises (SMEs) in Malaysia from various sectors. Respectively, results from this study indicate that the sustained use of CBBS is a key constituent that is required in order to promote and enhance organizational performance of SMEs in Malaysia.